Answer:
let me see and ill let you know
Step-by-step explanation:
<span>x^0 y^-3 / x^2 y^-1
= 1 / </span> x^2 y^-1 (y^3) ...because x^0 = 1 and [(y^-1) (y^3)] = y^2<span>
= 1/(x^2 y^2)</span>
Answer:
C. 15
Step-by-step explanation:
<h2>
<em><u>∠ADC=∠ABC/2=30/2=15</u></em></h2>
<span>2x/4x+2 x 14 x+7/6 is unclear. Do you mean 2/4x, or do you mean 2x
-------- ??
4x+2
Use parentheses to make things clearer.
I will assume that you meant to write
2x
--------- * 14x + 7/6
4x + 2
but am very much unsure if this is correct or not.
Perhaps you meant
</span>2x/(4x+2) times 14(x+7/6)
<span>
This comes out as follows:
2x * 14 (x + 7/6) 28x(x + 7/6) 14x(x + 7/6)
------------------------ = ------------------- = --------------------
4x+2 2(2x + 1) 2x + 1 after reduction.
Performing the multiplication, we get 14x^2 + 98/6
--------------------
2x+1
</span>
It appears that you're using "x" both as a variable name and as the "multiply" operator. If so, please don't! Use " * " to indicate multiplication.
<span>
</span>Please take and share a screen shot of this problem.
Answer:
X = 59
Step-by-step explanation:
2 × 59 = 118
18 + 18 + 59 + 59 = 154